The Influence of Sharia Marketing, Assets and Prices on Online Merchant Business Sustainability Due to The Closure of The Tiktok Shop in Banda Aceh - Muhazir, Muhazir; Kesuma, T.Meldi (Universitas Syiah Kuala, 2025)
This research aims to determine the influence of sharia marketing variables, assets and prices on the sustainability of online merchant businesses in Banda Aceh due to the closure of TikTok shops. This research uses quantitative research with a descriptive approach, while the objects in this research are the TikTok shop sellers in Banda Aceh. The data used in this research is primary data obtained from respondents who have filled out the questionnaire. The sample in this study was 105 respondents who were calculated using the Hair formula, the sample was taken using a non-probability sampling technique with a purposive sampling approach and the data was analyzed using a multiple linear regression model. The results show that simultaneously sharia marketing, assets and prices have an effect on business sustainability, while partially sharia marketing, assets and prices have a significant partial effect on business sustainability.